2023
DOI: 10.1155/2023/2801318
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Molecular Mechanism of the Antioxidant Activity of Medicine and Food Homology Licorice Flavonoids Based on Pharmacophore Theory and Quantum Calculations

Yi Hu,
Peiyi Liang,
Zhuxian Wang
et al.

Abstract: Licorice flavonoids are a kind of flavonoids extracted from the root of licorice, which have good antioxidant activity and are widely used in the food industry. In the early research of the research group, it has been found that the antioxidant activity of licorice flavonoids can be altered by solvent mediation. However, the molecular mechanism underlying the antioxidant properties of licorice flavonoids is still not fully understood. Therefore, this study aims to explore the molecular mechanism underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…20 This is all due to the ortho phenolic hydroxyl group contained in the protein. 21 In order to reduce the cost of extraction and synthetic method to make it suitable for large-scale industrial application, dopamine (DA) with the same functional group was found, which was combined with the polymer to realize the function of the material. 22 This provides a possible way to prepare and improve the friction and washing resistance of oil/water separation fabrics, and also lays a certain foundation for the research development and practical application of oil/water separation fabrics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 This is all due to the ortho phenolic hydroxyl group contained in the protein. 21 In order to reduce the cost of extraction and synthetic method to make it suitable for large-scale industrial application, dopamine (DA) with the same functional group was found, which was combined with the polymer to realize the function of the material. 22 This provides a possible way to prepare and improve the friction and washing resistance of oil/water separation fabrics, and also lays a certain foundation for the research development and practical application of oil/water separation fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, mussels that exist in the ocean can adhere firmly to rocks and the bottom of the ship by virtue of their secreted foot silk protein, and can form good bonds even in harsh marine environments 20 . This is all due to the ortho phenolic hydroxyl group contained in the protein 21 . In order to reduce the cost of extraction and synthetic method to make it suitable for large‐scale industrial application, dopamine (DA) with the same functional group was found, which was combined with the polymer to realize the function of the material 22 .…”
Section: Introductionmentioning
confidence: 99%